Tropomyosin-related kinase A (TrkA) inhibition for the treatment of painful knee osteoarthritis: results from a randomized controlled phase 2a trial - Watt, F; Blauwet, M; Fakhoury, A; Jacobs, H; Smulders, R; Lane, N (Elsevier, 2019)
Objective To investigate the TrkA inhibitor, ASP7962, for treatment of painful knee osteoarthritis.